The US Factor in Pakistan-Iran Relations: New Dimensions - Manzoor Ahmad; Tahir Ali; Zahir Shah (Journal of Political Studies, 2017)
Pakistan-Iran relations have been complex and uncertain due to United States tremendous influence since 9/11. National interest remains a dominant factor to form the core of bilateral ties between the states. The change of governments in these states resulted in to reassess the foreign policy which gave a new dimension to the suspected and hostile relations between both the Muslim States which successfully undermined the United States hegemonic pressure. This paper is an attempt to explore Pakistan’s foreign policy towards Iran after Musharraf Presidency till now and the factors due to which it deterred and challenged the US influence.